Hermetic Packaging of Sensor - Lim, Kok Seng (2016)
Two types of bonding were investigated in this study, which consist of Cu-Cu fusion bonding use of Ar/N plasma activation and Au-Al Thermocompression bonding. Both bonding are direct metal to metal bonding. Cu-Cu fusion bonding use of Ar/N plasma activation is a derivative, directed to lower processing temperatures for direct bonding with hydrophilic surfaces. Surface activation prior to bonding has the typical advantage that no intermediate layer is required and adequately high bonding energy is reached after annealing at a temperature that is below 400 °C. The reason for the decreasing of temperature of annealing the sample is such that using plasma activation on clean wafer surfaces will increase the bonding strength of the sample. To establish maximum surface energy at low temperatures numerous parameters for plasma activation and annealing need to be optimized according to the bond material.[1] Thermocompression bonding portrays a wafer bonding technique and is referred to as diffusion bonding. Diffusion bonding is a solid state welding technique, it is able to join similar and different metal. It works on the principle of solid state diffusion, wherein the atoms of two solid, metallic surfaces scatter themselves after some time. This is normally done by an increment of temperature.[2]